If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 5) = 3(y + -15) + 20 Reorder the terms: 2(5 + y) = 3(y + -15) + 20 (5 * 2 + y * 2) = 3(y + -15) + 20 (10 + 2y) = 3(y + -15) + 20 Reorder the terms: 10 + 2y = 3(-15 + y) + 20 10 + 2y = (-15 * 3 + y * 3) + 20 10 + 2y = (-45 + 3y) + 20 Reorder the terms: 10 + 2y = -45 + 20 + 3y Combine like terms: -45 + 20 = -25 10 + 2y = -25 + 3y Solving 10 + 2y = -25 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 10 + 2y + -3y = -25 + 3y + -3y Combine like terms: 2y + -3y = -1y 10 + -1y = -25 + 3y + -3y Combine like terms: 3y + -3y = 0 10 + -1y = -25 + 0 10 + -1y = -25 Add '-10' to each side of the equation. 10 + -10 + -1y = -25 + -10 Combine like terms: 10 + -10 = 0 0 + -1y = -25 + -10 -1y = -25 + -10 Combine like terms: -25 + -10 = -35 -1y = -35 Divide each side by '-1'. y = 35 Simplifying y = 35
| 4=(.300+x)(.200+x) | | 1/4(x-12) | | 15x+10y=90 | | -1/2(8+6) | | 15x+10x=90 | | 7(8-3)= | | k=k*11 | | -2z-4(10-4z)=-2 | | 36x+11=5x^2 | | -4(x-4)-2x=8-6(x+3) | | 3a-a+1=5 | | 5=2(3-8q)-2q | | 3[2+6(8-7)]= | | -1-2/7v2 | | -7=-(1-3a)-5a | | 4x+2=6x+9 | | 4(-9k+2)=k+5 | | -12x^2-35x=18 | | a-5(1+6a)=-6 | | 2-x=2x+2 | | 5=n-5(6n+2) | | 4x-2=6x+9 | | 7y+-24=4y+-63 | | 4k-(6-2k)=10 | | 1/6-1/2 | | 2z+3(-4+4z)=-3 | | cu+cv+du+dv= | | 6(n+4n)= | | 5x^2-6x+28=14 | | 0.71-(.22s)=1.03-0.62s | | 10s-2=9s+6 | | (am+bm)+(an+bn)= |